Catapult start likely improves sprint start performance - Nagahara, R.; Gleadhill, S. (International Journal of Sports Science & Coaching, 2022)
Sprint technical training, named the catapult start, is defined as partner assisted pulling of the hip backward at the set position and during block clearance, released by the forward motion of the athlete. This study investigated the characteristics of the catapult start and its influence on the following sprint start performance. Fourteen male sprinters performed a single 15-m control, catapult, and post-catapult sprint starts, during which ground reaction forces (GRFs) were measured using force platforms. All measured GRF variables during the block clearance, except for the impulses and mean forces on the front block and ratio of force for the rear block, were greater in the catapult start than the control (effect size [ES]=0.52?2.09). Waveform analyses revealed that the rear block anteroposterior GRF was greater for the catapult start than the control during the initial, middle and final phases (0 to 20%, 40 to 61% and 95 to 100%) of block clearance, while the rear block ratio of force was greater for the catapult start until 13% of block clearance. The catapult start resulted in greater rear block ratio of force (ES=0.28), faster 10-m sprint time (ES=0.31) and greater average horizontal external power during the initial 10-m (ES=0.25) at the post-catapult trial. The results suggest that the catapult start can be accompanied with greater force production mainly for the rear block regardless of direction during the block clearance, and it can improve post-catapult sprint start performance in terms of the rear block ratio of force and 10-m sprint time.